Colchicine Effectiveness and Safety in Periodic Fever, Aphthous Stomatitis, Pharyngitis, and Adenitis - Welzel, Tatjana; Ellinghaus, Maren; Wildermuth, Anna L.; Deschner, Norbert; Benseler, Susanne M.; Kuemmerle-Deschner, Jasmin B. (Frontiers in Pediatrics, 2021)
Introduction: Periodic fever, aphthous stomatitis, pharyngitis, and cervical adenitis (PFAPA) is the most common fever syndrome in childhood. High disease activity (DA) dramatically impacts the health-related quality of life. Thus, effective and safe treatment is crucial. Colchicine might be effective, but data are still lacking. Study aimed to assess colchicine safety and effectiveness in PFAPA. Methods: This single center study was conducted between 03/2012 and 05/2021 in PFAPA patients without variants in genetic panel testing aged <18 years fulfilling Marshal criteria and classification criteria of Gattorno et al. Exclusion criteria were elevated liver enzymes, impaired kidney function, celiac disease, lactose intolerance, previous/ongoing biologics, known colchicine-intolerance. Demographics, clinical characteristics, treatment, DA, colchicine effectiveness and safety were recorded at baseline, first and last visit. Colchicine was started at 0.5-1.0 mg/day. DA was captured by physician (PGA) and patient/parent (PPGA) global assessment on a 10 cm visual analogue scale, categorized as mild (<2), moderate (2–4) and high (≥5). Adverse event (AE) monitoring included gastrointestinal symptoms, liver enzyme/creatinine elevation, leukopenia, neutropenia. Primary outcome included response (R; composite of PPGA+PGA decrease ≥2) at last follow-up. Secondary outcomes were Partial Response (PR; PGA decrease =1+PPGA decrease ≥1), no response (NR; unchanged/worsened PGA/PPGA), colchicine safety, flare characteristics. Results: 27 PFAPA patients were included, 52% were female, median age was 5.8 years (1-10.75), median follow-up time was 13 months. At baseline, median PPGA was high; median PGA moderate. All patients had febrile flares. Median flare frequency was every 4-5 weeks; median duration 5-6 days. Nine patients were pre-treated with corticosteroids, increasing flare frequency in 8/9. Primary Outcome: 17 patients (63%) were responders. Secondary outcomes: PR was achieved in 15%; NR in 22% at last follow-up. DA decreased significantly (p<0.0001). At last follow-up, 52% reported no flares, median flare duration decreased to 1-2 days. At first follow-up, 22% reported mild abdominal pain/diarrhea. Moderate abdominal pain/diarrhea occurred with ≥1mg/day. Mild asymptomatic liver enzyme elevation/leucopenia were rare; no severe AE or colchicine discontinuation were observed. Conclusion: Colchicine seems to be safe, well-tolerated, and effective in PFAPA patients. It can be considered in children with moderate/high DA even those without corticosteroid-benefit.